2005
DOI: 10.1051/ject/200537381
|View full text |Cite
|
Sign up to set email alerts
|

Use of Platelet Gel and Its Effects on Infection in Cardiac Surgery

Abstract: The use of plasmapheresis in cardiac surgery has failed to show an unequivocal benefit. However, the further processing of plasmapheresed blood to obtain a platelet-rich concentrate, termed platelet gel, may reduce patient susceptibility to infection through poorly understood mechanisms related to a combination of platelets, white blood cell content, and expedited wound healing. The purpose of the study was to retrospectively evaluate the incidence wound infections in patients undergoing cardiac surgery. Plate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(7 citation statements)
references
References 15 publications
(15 reference statements)
0
6
0
Order By: Relevance
“…In the research that was utilised for the meta-analysis, 8961 CS persons were in the utilised researchers' starting point, 3663 of them were utilising PRP, and 5298 were control. [12][13][14][15][16][17][18][19][20][21][22] PRP had significantly lower SWI, deep SWI, and superficial SWI, compared to control in CS persons. However, when interacting with its values, caution must be taken since a low sample size of some of the nominated researchers was found for the comparisons in the meta-analysis (5 out of 11 <200 persons).…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…In the research that was utilised for the meta-analysis, 8961 CS persons were in the utilised researchers' starting point, 3663 of them were utilising PRP, and 5298 were control. [12][13][14][15][16][17][18][19][20][21][22] PRP had significantly lower SWI, deep SWI, and superficial SWI, compared to control in CS persons. However, when interacting with its values, caution must be taken since a low sample size of some of the nominated researchers was found for the comparisons in the meta-analysis (5 out of 11 <200 persons).…”
Section: Discussionmentioning
confidence: 79%
“…Eleven papers, published between 2005 and 2022, from a total of 1098 linked research that met the inclusion criteria were chosen for the research. [12][13][14][15][16][17][18][19][20][21][22] The consequences of these investigations are accessible in Table 2. 8961 CS persons were in the utilised researchers' starting point, 3663 of them were utilising PRP, and 5298 were control.…”
Section: Resultsmentioning
confidence: 99%
“…Potential positive clinical effects of these findings are confirmed in a study on the combined use of platelet gel and fibrin sealant in TKA which showed a statistically significant lower incidence of postoperative wound infections and postoperative leakage in the treatment group [11]. In cardiac surgery, a statistically significant lower incidence of superficial wound infections and deep sternal postoperative infections was also observed in the APG group [42]. Furthermore, in acute and chronic cutaneous wounds, and in diabetic neuropathic foot ulcers, the application of autologous APG was concluded to enhance the standard treatment [8, 21, 27, 31, 32].…”
Section: Discussionmentioning
confidence: 84%
“…Autologous platelet gel (APG), prepared from a unit of autologous fresh whole blood, is a small volume of plasma containing high concentrations of platelets, growth factors, leucocytes, vaso‐active substances, mixed with thrombin. The use of APG has been advocated to improve haemostasis, range of motion, wound healing, and bone growth in a variety of surgical disciplines [2–4, 10–14, 17–19, 21, 34, 42, 45].…”
Section: Introductionmentioning
confidence: 99%
“…There is also indication that PRP has infection-fighting properties. PRP has been shown to reduce the incidence of sternal infection (7), and it is now understood that platelets play a role in recruiting white blood cells (8) and release bactericidal factors (9). These revelations make PRP use in chronic wounds all the more attractive, because they are plagued by infection.…”
mentioning
confidence: 99%